Prevalence of heterophoria and associations with refractive error, heterotropia and ethnicity in Australian school children. Issue 5 (22nd October 2009) - Leone, Jody F; Cornell, Elaine; Morgan, Ian G; Mitchell, Paul; Kifley, Annette; Wang, Jie Jin; Rose, Kathryn A
Abstract : Aims: To establish the prevalence of heterophoria and its association with refractive error and ethnicity in a population-based study of Australian schoolchildren. Methods: The Sydney Myopia Study is a stratified, random cluster (school-based) sample of 4093 students (examined: 2003–2005). Two samples aged 6 (n=1692) and 12 years (n=2289) without heterotropia were included. Prevalent heterophoria was assessed using cover un-cover and prism bar alternate cover testing at 33 cm and 6 m distance fixation. Cycloplegic autorefraction (1% cyclopentolate) was performed. Significant refractive error was defined as ≤−0.50SE and ≥+2.00SE. Results: Exophoria was highly prevalent at near fixation (age 6: 58.3%, age 12: 52.2%). Orthophoria predominated at distance fixation (age 6: 85.4%, age 12: 90.9%). Hyperopia was associated with esophoria at near (age 6: OR 1.7, 95% CI 1.1 to 2.8, age 12: OR 2.9, CI 1.1 to 2.8) and distance fixation (age 6: OR 9.7, CI 3.5 to 26, age 12: 9.6 OR, CI 4.2 to 22). Myopia was associated with exophoria at near (OR 2.1, CI 1.5 to 2.7) and distance fixation (OR 3.1, CI 2.1 to 4.4) for 12-year-old children only. Exophoria was more frequent in children of East Asian than European Caucasian origins, even after adjusting for refraction; at near (age 6: OR 1.4, CI 1.0 to 2.0, age 12: OR 1.4, CI 1.0 to 1.9) and distance (age 12: OR 1.7, CI 1.1 to 2.7). Conclusion: Contrary to other studies, exophoria, not orthophoria, was predominant for near. Exophoria was more prevalent in children of East Asian origin. Longitudinal studies are needed to establish if incident heterotropia is preceded by heterophoria.